Roles of the Different Sub-Regions of the Insular Cortex in Various Phases of the Decision-Making Process - Droutman, Vita; Bechara, Antoine; Read, Stephen J. (Frontiers in Behavioral Neuroscience, 2015)
This paper presents a coherent account of the role of the insular cortex (IC) in decision-making. We follow a conceptualization of decision-making that is very close to one previously proposed by Ernst and Paulus (2005): that the decision process is a progression of 4 phases: (1) re-focusing attention, (2) evaluation, (3) action, and (4) outcome processing, and we present evidence for the insula’s role in all these phases. We review the existing work on insula’s functional anatomy that subdivides the IC into posterior, dorsal anterior and ventral anterior regions. We re-map the results provided by the existing literature into these subdivisions wherever possible, to identify the components' role in each decision making phase. In addition, we identify a self-regulating quality of the IC focused on harm avoidance.